Antecedentes y bases para un proyecto de produccion de semilla de yuca en la Costa Norte de Colombia - López M., J. (International Center for Tropical Agriculture, 1986)
Background information is given on a cassava seed production project to be carried out on the northern coast of Colombia to improve crop productivity in the region through the use of improved planting material. The proposed methodology includes a survey to determine seed quality problems and geographic distribution. Farmers should recognize the need for improved seed; therefore a pilot project should be conducted in (1) places where successful agroindustrial projects have been developed and (2) in places where decreasing cassava yields indicate production problems such as seed quality. Simultaneously, other activities like training, commercial seed production, basic seed multiplication, and meristem culture of regional var. will be conducted. On-farm seed selection will also be carried out. (CIAT)